Diagnostic accuracy of T2-hypointensity in determining the epileptogenic lesion on unmyelinated brain MRI in infants with tuberous sclerosis complex (TSC) - Ebel, Matyas; Stevering, Carmen H; Holubova, Zuzana; Lequin, Maarten H; Kyncl, Martin; Straka, Barbora; Hulshof, Hanna M; Jahodova, Alena; Kudr, Martin; Braun, Kees P J; Jansen, Floor E; Krsek, Pavel (Brain communications, 2025)
Identification of the epileptogenic lesion is challenging in tuberous sclerosis complex as multiple lesions might represent the seizure onset zone. A combination of dysplastic MRI features has diagnostic value in pre-surgical evaluation. However, these radiological characteristics may be difficult to identify and have not been studied on early unmyelinated brain MRI in tuberous sclerosis complex infants. Our study aimed to assess the diagnostic accuracy of T2-hypointense lesions on unmyelinated MRI in identifying the epileptogenic lesion. We included children with tuberous sclerosis complex who underwent resective or disconnective epilepsy surgery in the Motol University Hospital Prague and the University Medical Center Utrecht with available (i) unmyelinated MRI (before the age of 9 months), (ii) pre- and post-operative brain MRI and (iii) at least 2 years follow-up post-surgery. We identified T2-hypointense lesions and highly dysplastic lesions on unmyelinated or myelinated MRI, assessing their diagnostic accuracy in epileptogenic lesion identification by comparing seizure free to non-seizure free patients. Twenty-seven patients met inclusion criteria. We identified 54 T2-hypointense lesions in 24 patients, 30 were already highly dysplastic on unmyelinated MRI, showing cortical thickening and transmantle sign in most cases, while calcifications appeared later. Diagnostic accuracy of T2-hypointense (70.8%) was superior to the presence of the most dysplastic features (55.6%) in epileptogenic lesion identification. Positive predictive value for complete resection of all T2-hypointense lesions was 63.6%, compared to 50.0% for highly dysplastic lesions. Seizure recurrence was high (negative predictive value 76.9%) when T2-hypointense lesions remained outside the resected area. Assessing T2-hypointense lesions on unmyelinated brain MRI has important diagnostic value in identifying the epileptogenic lesion in pre-surgical work-up in infants with tuberous sclerosis complex and drug-resistant epilepsy. Unmyelinated brain MRI deserves a more important position in pre-surgical evaluation in infants with tuberous sclerosis complex and drug-resistant epilepsy.
Keywords: epilepsy surgery; TSC; myelination; MRI